Problem-based Learning Implementation Using Blended Learning on Environmental Pollution Concepts - Verla Ardiani; Much. Fuad Saifuddin (Universitas Sultan Ageng Tirtayasa, 2022)
Problem-based learning is a widely used learning model, but how to implement it using blended learning to overcome online learning in junior high school. This article focuses on finding out the effect of problem-based learning implemented by blended learning on students' motivation and learning outcomes. This studey used a quasi-experimental design. The research sample used two classes with a purposive sampling technique. The data collection technique used a post-test instrument test to see the learning outcomes and used a learning motivation questionnaire. The Mann-Whitney U-test of the learning outcomes showed the p-value is less than 0.05, which means that there is a significant difference on student learning outcomes due to the implications of the problem-based learning model with blended learning using Edmodo on environmental pollution. However, the Mann-Whitney U-test of the learning motivation showed the p-value is more than 0.05, which means that there is no a significant difference on student learning motivation due to the implications of the problem-based learning model with blended learning using Edmodo on environmental pollution